Predicting Parent Health-related Quality of Life in a Community Sample: a Cumulative Risk Model - (:unkn) unknown (My University, 2015)
National surveys estimate that nearly 30% of children have at least one chronic medical condition and the prevalence is likely to continue to increase. This trend has drawn attention to improving child and parent quality of life in families affected by pediatric chronic conditions. Health-related quality of life (HRQoL) of parental caregivers has been tied to poorer child functioning as well as parent mental health concerns across pediatric conditions. Several predictors of poor Parental HRQoL consistently emerge: single parent status; low socioeconomic status; poor general family functioning; lower child HRQoL; and a lack of social support. The current study evaluated the combined effect of multiple risk factors for poor parental HRQoL using a cumulative risk index (CRI). Such a model for parental functioning may provide a more systemic understanding of HRQoL in the context of pediatric chronic illness broadly. The current study compared linear and quadratic cumulative risk models in predicting parent HRQoL. A linear CRI model was found to account for variance in parent HRQoL beyond that accounted for by individual risk factors. The quadratic model of risk was not supported. Results indicate standard pediatric practice should involve a comprehensive evaluation of the relative risks in the parent’s environment because of the close relationship with child functioning.
Keywords: Cumulative Risk; Family Functioning; Health-related Quality of Life; Pediatric Chronic Illness